Evolving management of pectus excavatum based on a single institutional experience of 664 patients. - Haller, J A (1989)
Most pediatricians and family physicians believe that children with pectus excavatum require surgery only for cosmetic indications and then only in teenagers. We believe pectus excavatum should be repaired in childhood (1) to relieve structural compression of the chest and allow normal growth of the thorax; (2) to prevent pulmonary and cardiac dysfunction in teenagers and adults; and (3) to obviate the cosmetic impact that may cause a child to avoid sports and gymnastics. Preoperative CT scans now help select those children who need repair to prevent progressive deformities. Pulmonary function studies during vigorous exercise can document respiratory dysfunction in teenagers. These features are reversible if repair is completed before the pubertal growth spurt. The ideal age for repair is 4 to 6 years, which permits enough emotional maturity for a positive hospital experience and avoids later psychological effects. Repair at an earlier age has no operative advantages. Our operative technique consists of the removal of three to four overgrown costal cartilages, repositioning of the sternum with a transverse osteotomy, and internal support using the child's lowest normal ribs, avoiding any prosthetic support. To prevent recurrence in teenagers, we add a temporary bar beneath the sternum to prevent depression of the sternum from the weight of the chest-wall muscle mass. Six hundred sixty-four patients have been followed for 1 to 40 years; 95% have excellent long-term results and only 5% have mild to moderate recurrences. Our current techniques of patient selection and surgery will be presented.